Arterial stiffness index beta and cardio-ankle vascular index inherently depend on blood pressure but can be readily corrected. Issue 1 (January 2017) - Spronck, Bart; Avolio, Alberto P.; Tan, Isabella; Butlin, Mark; Reesink, Koen D.; Delhaas, Tammo
Abstract : Objectives: Arterial stiffness index β and cardio-ankle vascular index (CAVI) are widely accepted to quantify the intrinsic exponent (β0 ) of the blood pressure (BP)-diameter relationship. CAVI and β assume an exponential relationship between pressure ( P ) and diameter ( d ). We aim to demonstrate that, under this assumption, β and CAVI as currently implemented are inherently BP-dependent and to provide corrected, BP-independent forms of CAVI and β. Methods and results: In P = P ref e β0 [( d / d ref )-1], usually reference pressure ( P ref ) and reference diameter ( d ref ) are substituted with DBP and diastolic diameter to accommodate measurements. Consequently, the resulting exponent is not equal to the pressure-independent β0 . CAVI does not only suffer from this 'reference pressure' effect, but also from the linear approximation of (d P /d d ). For example, assuming β0  = 7, an increase of SBP/DBP from 110/70 to 170/120 mmHg increased β by 8.1% and CAVI by 14.3%. We derived corrected forms of β and of CAVI (CAVI0 ) that indeed did not change with BP and represent the pressure-independent β0 . To substantiate the BP effect on CAVI in a typical follow-up study, we realistically simulated patients ( n  = 161) before and following BP-lowering 'treatment' (assuming no follow-up change in intrinsic β0 and therefore in actual P – d relationship). Lowering BP from 160 ± 14/111 ± 11 to 120 ± 15/79 ± 11 mmHg ( p  < 0.001) resulted in a significant CAVI decrease (from 8.1 ± 2.0 to 7.7 ± 2.1, p  = 0.008); CAVI0 did not change (9.8 ± 2.4 and 9.9 ± 2.6, p  = 0.499). Conclusion: β and CAVI as currently implemented are inherently BP-dependent, potentially leading to erroneous conclusions in arterial stiffness trials. BP-independent forms are presented to readily overcome this problem. Abstract : Supplemental Digital Content is available in the text